Cervical Antibodies to Herpes Simplex Virus Proteins in Pregnancy and Puerperium: A Pilot Study. Issue 1 (1996) - Watts, D. Heather; Guise, Jeanne-Marie; Brown, Zane; Corey, Lawrence; Ashley, Rhoda L.
Abstract : Objective: This study was undertaken to evaluate the changes in total and anti-herpes simplex virus (HSV)-specific cervical IgA and IgG antibody profiles during and after pregnancy. Methods: Serum and cervical secretions were obtained from pregnant patients before 20 weeks gestation, at 34–36 weeks gestation, and at 6 weeks postpartum and tested for total IgA and IgG antibody and for IgA and IgG to HSV proteins by Western blot. Results: Seven women were HSV seronegative, 14 HSV-1 seropositive, and 14 HSV-2 ± HSV-1 seropositive. Minimal changes in the serum anti-HSV profiles were seen over the 3 visits. The total cervical IgA, IgG, and protein levels did not change between the 2 pregnancy visits but tended to increase at the postpartum visit. No consistent change in cervical HSV-specific IgA and IgG was seen during pregnancy, but the levels increased markedly at the postpartum visit. Conclusions: Lower cervical anti-HSV antibody levels may be related to the previously reported increased frequency of a reactivation of HSV during late pregnancy. Further evaluation is necessary to confirm and quantify the changes in genital immunity during pregnancy and to evaluate whether the increased levels at the postpartum visit are sustained.